Briefcase Recitation System with Random Name Generator: An Alternative Recitation Tool - Alejandro, Leonard Luis (International Journal of Computing Sciences Research; Vol 1 No 2 (2017): Vol 1, No 2, 2017)
Purpose – This research focused on the development, design, and application of the Briefcase Recitation system to lessen the problems encountered in the traditional way of classroom questioning. Method – This study embeds the use of technology inside the classroom and is patterned after the popular “Deal or No Deal” game show. The system includes a random student name generator to pick the student who will answer randomized questions enclosed in briefcases within a specific time limit. Answers to questions are assessed and scored by the teacher using a rubric.  Waterfall Model was used in developing the system and comprised of six modules, i.e., Questions, Participant, Databank, Scores, Timer, and Reports. The system was tested and evaluated using ISO 2196 Software Quality Model by 17 professors from Computer Science and Education Departments of Adamson University. Results – The respondents assessed Briefcase Recitation System as highly adaptable which means that the system is functioning well and the features found in six modules are well presented. The respondents strongly agreed that Briefcase Recitation System is highly effective and adaptable in terms of functionality, reliability, usability, efficiency, maintainability, and portability. They also evaluated the system as an effective tool in improving classroom participation. Conclusion – The Briefcase Recitation System can be used as an alternative tool in improving classroom participation of students. Practical Implication – This research implies that there is a need for teachers to continuously innovate classroom activities such as classroom recitation.